Entrepreneurial Orientation and Innovation Ability on MsMEs Performance: The Moderator Role of Social Network Ties - Munif, Dikka Abdillah Rizqia Putra; Priyono, Anjar (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2024)
This study aims to test and analyze the effect of entrepreneurial orientation and innovation ability on the performance of MSMEs, as well as to test and analyze the effect of entrepreneurial orientation on MSME performance in moderation of social network ties, test and analyse the effect of innovation capability on MSME performance in moderation of social network ties. This type of survey will be used in this research. With the technique used in sampling using cluster sampling, this study involved 98 MSMEs in Sleman Regency, Yogyakarta Special Region (DIY). Using analytical tools in the form of PLS-SEM, the results of this study indicate that 1) there is an effect of entrepreneurial orientation on MSME performance, 2) there is no effect of innovation capability on MSME performance, 3) there is no effect of entrepreneurial orientation on MSME performance moderated by social network ties, 4) there is no effect of innovation capability on MSME performance moderated by social network ties. The implications of the results of this study can be a reference, recommendation, benefit, and insight for MSME actors to analyze the results of this study and identify the influence of entrepreneurial orientation and innovation capabilities, as well as the moderating role of social network ties so that it is expected to have an impact on MSME performance.